Gambaran Succesful Aging pada Lansia (Studi Kasus di Desa Cangaan Kecamatan Ujung Pangkah Kabupaten Gresik) (Overview of Successful Aging in the Elderly (A Case Study in Cangaan Village, Ujung Pangkah District, Gresik Regency) - Afnah, Al Fanani Laila (Happiness: Journal of Psychology and Islamic Science, 2025)
In general, elderly people experience physical changes from being previously healthy, strong, to becoming physically weak as a person gets older. Most elderly people want to live prosperously in old age where their basic needs are met. To achieve successful aging, you need to prepare yourself long before entering that phase. So, it is important for all elderly people to live every aspect of life, whether physical, psychological and social, in a balanced way. This research was located in Cangaan Village, Ujung Pangkah District, Gresik Regency. The aim of this research is to determine the description of successful aging and the factors that play a role in successful aging in the elderly in Cangaan Village, Ujung Pangkah District, Gresik Regency. This research uses a qualitative research method with a case study approach. In collecting research data, researchers used observation, interviews and documentation methods. The results of this study show that the picture of successful aging in the elderly: the four elderly people optimize their ability to achieve successful aging by choosing to continue working, the elderly have good physical and psychological conditions, even though they have a history of illness, the elderly are still able to carry out good activities, and have short-term memory. among the elderly, elderly people also admit that they feel happy and have their own satisfaction in living their lives, there are also those who admit that they feel lonely in living their old age.